Managing quality and customer trust in the e-retailing servicescape. (2017) - Bateman, Patrick J.; Ulusoy, Emre; Keillor, Bruce D.
As online consumer shopping continues to grow, so does the importance of a website in a retailer's strategy. In this increasingly competitive environment, building customer loyalty and retaining customers is integral to achieving sustained profitability. While one stream of literature has suggested that e-retailers should concentrate on improving quality, another has recommended the focus should be on building trust with customers. The objective of this study is to synthesise these streams, investigating how the interplay between three forms of quality (information, system, and service) and trust help retain customers in a virtual servicescape. Integrating information systems and marketing research, the results suggest trust mediates the relationship between each type of quality and both satisfaction and repurchase intentions. Furthermore, of the three types of quality, service quality engenders the greatest impact on trust, followed by information then system quality. The paper concludes with a discussion of this model for managers and researchers.